Structure-function analysis of Lyn kinase association with lipid rafts and initiation of early signaling events after Fcepsilon receptor I aggregation - Kovárová, M; Tolar, P; Arudchandran, R; Dráberová, L; Rivera, J; Dráber, P (Molecular and cellular biology, 2001)
The first step in immunoreceptor signaling is represented by ligand-dependent receptor aggregation, followed by receptor phosphorylation mediated by tyrosine kinases of the Src family. Recently, sphingolipid- and cholesterol-rich plasma membrane microdomains, called lipid rafts, have been identified and proposed to function as platforms where signal transduction molecules may interact with the aggregated immunoreceptors. Here we show that aggregation of the receptors with high affinity for immunoglobulin E (FcepsilonRI) in mast cells is accompanied by a co-redistribution of the Src family kinase Lyn. The co-redistribution requires Lyn dual fatty acylation, Src homology 2 (SH2) and/or SH3 domains, and Lyn kinase activity, in cis or in trans. Palmitoylation site-mutated Lyn, which is anchored to the plasma membrane but exhibits reduced sublocalization into lipid rafts, initiates the tyrosine phosphorylation of FcepsilonRI subunits, Syk protein tyrosine kinase, and the linker for activation of T cells, along with an increase in the concentration of intracellular Ca(2+). However, Lyn mutated in both the palmitoylation and myristoylation sites does not anchor to the plasma membrane and is incapable of initiating FcepsilonRI phosphorylation and early signaling events. These data, together with our finding that a constitutively tyrosine-phosphorylated FcepsilonRI does not exhibit an increased association with lipid rafts, suggest that FcepsilonRI phosphorylation and early activation events can be initiated outside of lipid rafts.
Keywords: Protein Binding; transfekce; Recombinant Proteins; Calcium; receptory IgE; Enzyme Activation; Sphingolipids; Membrane Microdomains; antigeny; Protein Structure, Tertiary; konfokální mikroskopie; Structure-Activity Relationship; fragmentace DNA; terciární struktura proteinů; vápník; fosforylace; fosfotyrosin; Transfection; Receptors, IgE; Palmitic Acid; signální transdukce; Cholesterol; Phosphorylation; Phosphotyrosine; kyselina palmitová; src-Family Kinases; metabolismus lipidů; Tyrosine; Signal Transduction; membránové mikrodomény; tyrosin; vztahy mezi strukturou a aktivitou; skupina kinas odvozených od src-genu; Antigens; Microscopy, Confocal; luminescentní proteiny; krysa rodu Rattus; rekombinantní proteiny; vazba proteinů; sfingolipidy; cholesterol; Cell Membrane; zelené fluorescenční proteiny; Animals; DNA Fragmentation; Immunoblotting; Detergents; konformace proteinů; zvířata; precipitinové testy; Lipid Metabolism; buněčná membrána; časové faktory; Myristic Acid; Rats; Green Fluorescent Proteins; myši; DNA; aktivace enzymů; imunoblotting; oktoxynol; Luminescent Proteins; Protein Conformation; kyselina myristová; Mice; Octoxynol; Precipitin Tests; Time Factors; detergenty